Hubungan Mental health literacy dengan help-seeking attitudes pada Mahasiswa dalam Pemanfaatan Layanan Konseling di Perguruan Tinggi - Rifqa Aulia Hafifuddin; Iyulen Pebry Zuanny (Yayasan Azhar Amanaa Yogyakarta, 2026)
College students’ mental health requires attention because university life often involves academic pressure, social adjustment, and the developmental demands of emerging adulthood. Although universities commonly provide counseling services as a form of support, service availability does not necessarily lead to students’ willingness to use them. This study examined the relationship between mental health literacy and help-seeking attitudes among students in the context of utilizing university counseling services. A quantitative correlational design was employed with 344 students. Data were collected using the Mental Health Knowledge Schedule (MAKS) and the Attitudes Toward Seeking Professional Psychological Help-Short Form (ATSPPH-SF). Because the data were not normally distributed, the hypothesis was tested using Spearman’s correlation. The analysis revealed a significant positive relationship between mental health literacy and help-seeking attitudes (r = .259; p < .01). Students with better mental health literacy therefore tended to hold more favorable attitudes toward professional help-seeking, including help offered through university counseling services. Although the relationship was weak, mental health literacy may provide an important foundation for students’ acceptance of counseling. As actual service use was not measured, these findings should be interpreted as reflecting attitudinal readiness that may support service utilization